Global commodity markets and rebalancing in China: The case of copper - Jeannine N. Bailliu; Doga Bilgin; Kun Mo; Kurt Niquidet; Benjamin Sawatzky (Bank of Canada, 2019)
Given that China accounts for about half of global copper consumption, it is reasonable to expect that any significant change in Chinese copper consumption will have an impact on the global market. This paper examines the likely impact of the rebalancing of the Chinese economy on its copper consumption over the next decade, focusing on the relationship between the copper intensity of GDP and the share of investment in GDP. We use a panel smooth transition regression model to account for potential non-linearities in this relationship at different levels of urbanization and income. Our findings suggest that there is indeed a significant relationship between a country's copper intensity of GDP and its investment share. Our baseline rebalancing scenario for China implies that copper intensity in China has already peaked and is expected to decline steadily through the next decade. This anticipated reduction in Chinese copper intensity is the result of the dampening impact of rebalancing and higher per capita income on copper intensity, which more than offsets the upward pressure stemming from the ongoing process of urbanization. An exploration of alternative rebalancing scenarios suggests that China's rebalancing path could have a significant impact on global copper consumption.
Keywords: O13; O14; Q02; 330; International topics; Econometric and statistical methods